EFFECTIVE TECHNIQUES FOR MANAGING WORKPLACE STRESS AMONG EMPLOYEES IN THE MODERN ERA - Dhingra, Arti; Barkha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In today’s fast-paced and highly demanding work environment, employee stress has become an increasingly prevalent issue, adversely affecting both individual well-being and organizational productivity. This paper reviews various theoretical frameworks and evidence-based stress management techniques that can help mitigate stress among employees. Key strategies include cognitive-behavioral techniques, time management, mindfulness practices, and organizational support systems. By examining these approaches, this paper highlights effective methods for reducing stress and enhancing overall employee well-being. The study provides practical recommendations for organizations to incorporate into their employee wellness programs to promote a healthier, more productive work environment.